Structural safety of rolled and welded beams subjected to lateral‐torsional buckling - Kudzys, Antanas; Lukoševičienė, Ona; Baltrukėnaitė-Kroškienė, Inga (Journal of Civil Engineering and Management, 2010)
The expediency of using probability‐based approaches in the analysis of beams subjected to lateral‐torsional buckling is discussed. The values of buckling resistance moments and their uncertainties for rolled and equivalent welded I sections as particular members of the designed structures are analyzed. The safety margins of buckling steel sections exposed to permanent and variable vertical loads are modeled. The survival probability and reliability index of sections exposed to lateral‐torsional buckling are considered. The prediction of probability‐based safety of rolled and welded beams in buildings and civil engineering works are provided and illustrated by numerical examples. First Published Online: 24 Jun 2011